2014
DOI: 10.1039/c4cp00949e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the ionic size of small quaternary ammonium BF4 salts on electrochemical double layer capacitors

Abstract: By varying the cation size of quaternary ammonium salts, approximately 10% higher capacitance was achieved with trimethylethylammonium BF4 and trimethylpropylammonium BF4 relative to tetraethylammonium BF4 using microporous activated carbon (AC) electrodes. The ions carried solvation shells in the bulk electrolytes, but became desolvated within the narrow AC pores when the electrochemical double-layer capacitor was charged to a high potential. The capacitance depended on the size of the cation rather than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…59,68 On the one hand, Please do not adjust margins Please do not adjust margins research has identified that the ionic size and type of different salts have great influences on the capacitance and power performance of EDLCs. [69][70][71] It was observed that quaternary ammonium salts with small cations could achieve a high EDLC specific capacitance. 69 Furthermore, the salt also plays an important role in affecting the electrochemical window of organic electrolytes.…”
Section: Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…59,68 On the one hand, Please do not adjust margins Please do not adjust margins research has identified that the ionic size and type of different salts have great influences on the capacitance and power performance of EDLCs. [69][70][71] It was observed that quaternary ammonium salts with small cations could achieve a high EDLC specific capacitance. 69 Furthermore, the salt also plays an important role in affecting the electrochemical window of organic electrolytes.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…[69][70][71] It was observed that quaternary ammonium salts with small cations could achieve a high EDLC specific capacitance. 69 Furthermore, the salt also plays an important role in affecting the electrochemical window of organic electrolytes. 63,72,73 The ionic liquid, N-butyl-Nmethylpyrrolidinium bis(trifluoromethanesulfonyl) imide (PYR14TFSI) was used to formulate the electrolyte, and EDLCs containing PYR14TFSI in PC exhibited a high operating voltage (up to 3.5 V) and excellent cycling stability.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…The conductivity is affected by the size of the ion, the structure of the alkyl chain, and the viscosity of the electrolyte solution. We did not observe a relationship between the conductivity and capacitance [13,14] For example, the conductivity of C6 is 10% lower than that of C8, as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 71%
“…These electrolytes also responded rapidly during the discharge cycle, as evidenced by the high discharge currents in the early stages of the discharge cycle. This CV curve feature is characteristic of small and mobile cations [13]. The LSV curves obtained using the electrolytes (Fig.…”
Section: Resultsmentioning
confidence: 88%